Pembiayaan Murabahah Pada Perbankan Syariah di Indonesia - Surayya Fadhilah Nasution (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2021)
The research purpose to find out how is murabahah financing in Indonesia Islamic banking. The research method is used in the form of library research which collecting data by using written materials. Islamic banking has two intermediation functions. First, Islamic banking raise funds from the people and second, Islamic banking distribute funds via financing. One of Islamic banking financing is murabahah. Murabahah is selling/purchasing transaction with the agreed profit. Murabahah characteristic is the seller has to tell to the buyer about product purchase price and agreed profit. Murabahah has two ways, murabahah with order and without order. The survey results shown that Islamic banking has applied murabahah as their main financing. Keywords: Islamic banking, financing, murabahah.